Acute Effects of Self-Myofascial Release Through Foam Roller and Static Stretching Methods on Vertical Jump Performance of Taekwondo Players (Journal of Pharmaceutical Negative Results, 2022)
The objective of this research is to examine the acute effects of self-myofascial release through foam roller and static stretching methods on the vertical jump performance of taekwondo players. In this cross-sectional study, a randomized controlled experimental method, one of the quantitative research models, was used. 21 taekwondo players participated in this research voluntarily. The mean age of the participants was 15.95±,865; the mean height was 172.90±3,846 and the mean body weight was 61,86±5,379. On the first day of the study, low-paced jogging was performed for 5 minutes at a heart rate of 120 (RS V800) and then their vertical jump performance was measured. On the second day of the research, low-paced jogging was performed for 5 minutes, and then a static stretching protocol was applied to taekwondo players, and then their vertical jump performance was measured. On the third day of the research, low-paced jogging was performed for 5 minutes and then self-myofascial release through foam roller protocol was applied to taekwondo players and then their vertical jump performances were measured. As a result of the research, it was determined that there was no statistical difference between 5 minutes of jogging at a slow pace and static stretching. However, it was determined that there were statistically significant differences both between 5 minutes of jogging at a slow pace and self-myofascial release and between static stretching and self-myofascial release (p<0.05). In conclusion, it can be said that self-myofascial release through foam roller exercises can affect vertical jump performance positively and at an acute level.